2020
DOI: 10.1111/emip.12413
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐Based EFL Writing Error Analysis Using Human and Computer‐Aided Approaches

Abstract: Committing errors is expected in the development of language acquisition and learning; however, there is limited research that contributes to the literature on the effect of gender of English as a foreign language (EFL) writing. This study explored the gender differences in EFL students' writing using two approaches: human evaluation and computer-aided error analysis (CEA). A corpus of 90,753 words was compiled from written samples collected from 197 participants (98 males and 99 females [freshmen or sophomore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Likewise, in a study done by Pouladian et al (2017) to examine writing errors made by Iranian EFL learners, it was asserted that the male students made more speaking and writing errors than the female ones. Contrarily, in another study (Almusharraf & Alotaibi, 2021), no statistically significant difference was found between the total number of writing errors detected for the male and female students.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Likewise, in a study done by Pouladian et al (2017) to examine writing errors made by Iranian EFL learners, it was asserted that the male students made more speaking and writing errors than the female ones. Contrarily, in another study (Almusharraf & Alotaibi, 2021), no statistically significant difference was found between the total number of writing errors detected for the male and female students.…”
Section: Discussionmentioning
confidence: 77%
“…Some studies investigating gender differences on writing errors have been carried out, but they have pointed out different results. For instance, Almusharraf and Alotaibi (2021) found no statistically significant difference between the total number of writing errors detected for the male and female students. Boroomand and Rostami Abusaeedi (2013); however, reported that female EFL students made more writing errors than the male students did.…”
Section: Introductionmentioning
confidence: 78%
“…The primary benefit of Error Analysis is that it successfully transforms an error from a negative to a positive norm (Almusharraf & Alotaibi, 2021). Errors are now seen as students' constructive contributions to their second language learning rather than as "undesirable forms" (Kearney & Ellis, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pretrained NLP models can also be applied to the texts to create theoretically meaningful features. For example, in automated essay scoring, theoretical meaningful features such as the number of grammatical errors (Almusharraf & Alotaibi, 2020), text complexity (Sheehan, 2017), and text cohesion metrics (McNamara et al., 2010) can be first extracted using various pretrained/theoretically defined NLP models. The features can later be used in more specific ML models to score essays.…”
Section: Introduction To Machine Learningmentioning
confidence: 99%